Digital Space Sexual and Gender-Based Violence (SGVB): A Project for Empowering Girls and Women to Address and Respond - Dilogini, S. (University of Jaffna, 2024)
Sexual and Gender-Based Violence (SGBV) in cyberspace is a growing issue, with online platforms increasingly serving as arenas for harassment, exploitation, and discrimination. Women and girls in marginalized regions, such as Jaffna, Sri Lanka, face heightened challenges due to limited knowledge of digital safety and inadequate legal protections. To address these concerns, save a Life NGO, supported by the Embassy of the Netherlands, launched an 18-month project titled “Empowering Girls and Women in Jaffna to Effectively Address and Respond to Sexual and Gender-Based Violence in Cyberspace” on August 1, 2024. The initiative aims to raise awareness, equip participants with essential digital safety skills, and foster proactive responses to online SGBV.
Keywords: Community-level; Digital space SGBV; Empowering Girls and Women; Training of trainers (TOT); Workshop sessions